Effects of the Distance between Two Feet on Static Standing Balance Function in Convalescent Hemiplegic Patients with Stroke - Zixian XIAO; Qian CHEN; Dianhuai MENG (康复学报)
Objective:To study the effects of the distance between two feet on static balance function in convalescent hemiplegic patients with stroke, and to provide theoretical basis for balance training.Methods:Thirty convalescent stroke patients(17 male and 13 female)were evaluated using Pro-Kin balance training instrument with eye open and closed in three standing states: two feet side by side, 50 cm and a proper distance. The main measurement parameters included the standard deviation of longitudinal swing(SDoLS), the standard deviation of horizontal swing(SDoHS), mean longitudinal velocity(MLV, mm/s), mean horizontal velocity(MHV, mm/s), the ellipse area of motion(EAM, mm2)and the length of motion(LM, mm).Results:1)In the condition of eyes opening, some parameters of standing with feet 50 cm apart were significantly lower than those with feet side by side, including SDoHS[3(1.94, 5)], MLV[8.75(6, 13.25)mm/s], EAM[185.5(94.75, 447)mm2](P<0.05);in the condition of eyes closing, some parameters of standing with feet 50 cm apart were significantly lower than those with feet side by side, including SDoHS[3(2, 4)], EAM[326.5(142.25, 557.25)mm2]and LM[297(215.94, 455.5)mm](P<0.05).2)In the condition of eyes opening, some parameters of standing with feet proper distance were significantly lower than those with feet side by side, including SDoHS[3(2, 5)], MLV[8.69(5, 14)mm/s], MHV[6.32(4, 10)mm/s], EAM[186(97, 446.5)mm2]and LM[196(143.5, 306.25)mm](P<0.05);in the condition of eyes closing, some parameters of standing with feet proper distance were significantly lower than those with feet side by side, including SDoHS[3(2, 5)], MHV[7(4.44, 12.25)mm/s], EAM[275(145.25, 388.75)mm2], LM[287(216, 478.25)mm](P<0.05).3)In the condition of eyes opening, some parameters of standing with feet proper distance were significantly lower than those with feet 50 cm apart, including MHV[6.32(4, 10)mm/s]and LM[196(143.5, 306.25)mm](P<0.05);in the condition of eyes closing, some parameters of standing with feet proper distance were significantly lower than those with feet 50 cm apart, including MHV[7(4.44, 12.25)mm/s]and EAM[275(145.25, 388.75)mm2](P<0.05).Conclusion:There is a proper distance between two feet for convalescent stroke patients, in which their static standing balance is the most stable.